LICHENE DIKAWASAN TAHURA POCUT MEURAH INTAN - Srihandina, Apri; Afifah, Nur; Hafiz, Mutia; Ramadhana, Salsabilla; Amin, Nurdin (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2024)
Lichens are symbiotic organisms formed by the association between fungi and algae or cyanobacteria, playing a crucial role in ecosystems as indicators of environmental quality due to their sensitivity to pollution and climate change. These organisms are found in various habitats, including forests, rocks, and soil, and are capable of adapting to extreme environments. In the Pocut Meurah Intan Forest Park area, lichens thrive in high-humidity zones and supportive microhabitats, reflecting the forest ecosystem's health. Besides contributing to decomposition processes and providing nutrients to other plants, lichens are also vital for scientific research, particularly in understanding the impacts of climate change and pollution. This study aims to identify and document the diversity of lichen species in this area. A field survey method using purposive sampling was employed to collect samples from various locations with differing microhabitats. The results reveal significant variations in lichen species, indicating diverse microhabitat conditions and supporting ecosystem sustainability. This study provides fundamental information beneficial for conservation efforts and natural resource management in the area